Asymmetric impact of real effective exchange rate changes on~domestic output revisited: evidence from Egypt - Mesbah Fathy Sharaf; Abdelhalem Mahmoud Shahen (International Trade, Politics and Development, 2023)
Purpose This paper investigates the asymmetric impact of the real effective exchange rate (REER) on Egypt's real domestic output from 1960 to 2020. Design/methodology/approach A Nonlinear Autoregressive Distributed Lag (NARDL) model is utilized to isolate real currency depreciations from appreciations and account for the potential asymmetry in the impact of the REER. The analyses account for the various channels via which the REER could affect domestic output. Findings Results show evidence of a long-run asymmetry in the output effect of REER changes in which only real currency depreciations have a contractionary impact on output, while the REER has no impact on output in the short run. Practical implications The Egyptian monetary authority cannot rely on domestic currency depreciation as a policy instrument to boost domestic output. Originality/value Unlike most of the previous studies, which assume linearity in the impact of the REER on output, we relax this assumption and hypothesize that the REER changes have an asymmetric effect on the Egyptian domestic output in Egypt. We use a long time span from 1960 to 2020 and control for the potential structural breaks in the REER-output nexus and the various channels through which the REER can affect domestic output.
Keywords: E63; F31; F41; F62; 330; Asymmetric effects; Domestic output; Egypt; ARDL; Real effective exchange rate